Odpowiedzi

2010-04-10T19:09:57+02:00
{y=2x-4
8-4x=-2y
{-2x=-4-y
8+2(-4-y)=-2y
{2y=4+y
8-8-2y=-2y
{2x=4+y
0=-2y
{2x=4+0/:2
y=0
{y=0
x=2


{x-5y-5=0
3x+y-1=0
{x=5y+5
y=-3x+1
{x=5(-3x+1)
y=-3x+1
{x=-15x+5
y=-3x=1
{16x=5
y=-3x+1
{x=5/16
y=1-3/4=1/4
2010-04-10T19:11:06+02:00
Y= 2x-4
8-4x= -2y

y=2x-4
8-4x=2x-4

y=2x-4
6x=12

x=2
y=2*2 -4

x=2
y=0

spr
L₁=0 P₁ = 2*2 - 4 = 0
L₂=8-4*2 = 0 P₂= -2*0 = O



6x - 5=4y
2-4y=-6x

6/4x - 5/4 = y
2- 4*(6/4x - 5/4) = -6x

6/4x - 5/4=y
2-6x +5 = -6x

6/4x - 5/4 = y
0=7
SPRZECZNOŚĆ

2010-04-10T19:17:00+02:00
Y=2x-4
8-4x=-2y
-2x=-4-y
8+2(-4-y)=-2y
2y=4+y
8-8-2y=-2y
2x=4+y
0=-2y
2x=4+0/:2
y=0
y=0
x=2

Drugi przykład jest źle przepisany

x-5y-5=0
3x+y-1=0
x=5y+5
y=-3x+1
x=5(-3x+1)
y=-3x+1
x=-15x+5
y=-3x=1
16x=5
y=-3x+1
x=5/16
y=1-3/4=1/4